Effects of high intensity running to fatigue on isokinetic muscular strength in endurance athletes - Denadai, Benedito Sergio [UNESP]; Greco, Camila Coelho [UNESP]; Tufik, Sergio; de Mello, Marco Tulio (IOS Press, 2007)
The objective of this study was to examine the effects of high intensity exhaustive running exercise on the muscular torque capacity of the knee extensors for two types of contraction (concentric and eccentric) at different angular velocities (60 and 180 degrees/s) in well-trained runners. Eleven male runners specialized in middle and long-distance running volunteered to participate in this study. Initially each subject performed, on different days, two familiarization sessions on an isokinetic dynamometer and an incremental treadmill test to volitional exhaustion to determine the velocity associated with the onset of blood lactate accumulation (OBLA). The subjects then returned to the laboratory on two occasions, separated by at least seven days, to perform maximal isokinetic knee contractions at each of the velocities under eccentric (Ecc) and concentric (Con) conditions. Conducted randomly, one test was performed after a standardized warm-up period of 5 min at 50% VO2 max. The other test was performed 15 min after continuous running at OBLA until volitional exhaustion. Following this high intensity exercise there was a significant reduction of Con at 60 degrees/s and a significant reduction of Ecc at both velocities. Percent strength losses after running exercise were significantly different between contraction types only at 180 degrees/s. We can conclude that the reduction in isokinetic peak torque of the knee extensors after a session of high intensity exhaustive running exercise at OBLA depends on the contraction type and angular velocity.
Keywords: concentric; eccentric; angular velocity; aerobic exercise; fatigue